RELIGIOUS FUNDAMENTALISM AMONG STUDENTS - Benny Prasetiya; Ulil Hidayah; Robiatul Adawiyah (Conciencia, 2020)
This study aims to explain the religious orientation recognized by fundamentalism among students. This research can provide a comprehensive picture and answer regarding the attitude of Islamic fundamentalism. The research approach used is descriptive quantitative research. The method used in this research is the descriptive method. A descriptive method that aims to test a theory and provides a statistical picture with a percentage to show a description of the research data. Researchers took research samples through a random sampling technique of 100 respondents who are actively involved as Rohis activists from five high schools (SMAN/SMKN and MAN). The data analysis produced in this study is a descriptive statistical technique. Descriptive statistical analysis is used to analyze data by describing or describing the collected data as it is without intending to make generalized conclusions or generalizations. The results of the distribution show that some students are classified as having a high Fundamentalist Attitude, and a few others have a very high Fundamentalism Attitude. There are 4 people (4%) who have moderate fundamentalism.